2019
DOI: 10.1111/deve.12206
|View full text |Cite
|
Sign up to set email alerts
|

Wage Penalty for Temporary Workers in Turkey: Evidence From Quantile Regressions

Abstract: The paper estimates the wage gap between employees with different contract types in Turkey. We first employ a quantile regression method and then decompose wage differentials along the distribution. Our results indicate that nonpermanent contract holders are more common among the low-skilled and low-wage group. The findings imply a non-monotone pattern in Turkey where both sticky floor and glass ceiling effects are observable. These effects are persistent over time as both bottom-and topearner temporary worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Moreover, we define lower and upper tier informal sector workers not only by self-employment but also by the irregularity of contracts. Temporary, casual workers and workers with no contracts might be subject to double penalty in the informal sector as their wages are expected to be lower than permanent contract holders even in formal employment (Duman, 2019). Irregular workers also have much lower chances of obtaining a formal sector job especially if they are unskilled, which is clearly the case in Turkey.…”
Section: Review Of Informal Employment and Its Evolution In Turkeymentioning
confidence: 99%
“…Moreover, we define lower and upper tier informal sector workers not only by self-employment but also by the irregularity of contracts. Temporary, casual workers and workers with no contracts might be subject to double penalty in the informal sector as their wages are expected to be lower than permanent contract holders even in formal employment (Duman, 2019). Irregular workers also have much lower chances of obtaining a formal sector job especially if they are unskilled, which is clearly the case in Turkey.…”
Section: Review Of Informal Employment and Its Evolution In Turkeymentioning
confidence: 99%
“…Ampirik uygulamalar incelendiğinde genellikle kalıcı işlerde çalışanlara göre geçici işlerde çalışanların ücretlerinin daha düşük olduğu, başka bir ifade ile geçici işlerin bir ücret cezalandırmasına yol açtığı ortaya çıkmıştır. Kantil regresyon yönteminin kullanıldığı çalışmalarda (Bosio, 2014;Comi & Grasseni, 2012;Duman, 2019;Lass & Wooden, 2019;Le & NguŁyen-Huu, 2016)…”
Section: Literatür öZetiunclassified
“…While a number of researchers argue that various benefits can accrue to employees in non-standard positions, such as better reconciliation of work and life and higher control over work schedules, it is shown that the positive effects are highly dependent on the context and atypical jobs, on average, have lower pay and less security (Booth et al, 2002;Gash and McGinnity, 2007;Cazes and de Laiglesia, 2015). Across a number of countries, large and persistent wage gaps exists between different types of contract holders (Duman, 2019;Garnero et al, 2016). Moreover, employees in precarious positions are subject to lower protection by labor legislation and union membership because of higher turnover and lack of integration of such workers into the collective bodies (Vosko et al, 2009;Grimshaw, 2011).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…However, female employees at the beginning of their career are subject to higher risks of unemployment even when they have the same education with their male counterparts with fixed-term contracts (Kurz, 2002). With regards to wage effects of several types of NSE, sizable pay gaps across contract types in developed and developing countries are found, and it is shown that the earning differentials are not equal across genders (Duman, 2019;Cazes and de Laiglesia, 2015;Kahn, 2016;Gash and McGinnity, 2007). However, it should be noted that there is no agreement on the direction of the effect, as there are studies pointing out wage penalties as well as wage premiums for NSE, which also change along the distribution (Fuller and Vosko, 2008;Lass and Wooden, 2019).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation